The First Case of L. pseudomesenteroides Pulmonary Infection and Literature Review - Liwan Dai; Yishi Li; Xiaobing Zhang; Ming Ding; Shuliang Guo (Case Reports in Pulmonology)
L. pseudomesenteroides is a very rare bacterium that infects human beings, and it has been used as an industrial fermentation bacterium. At present, only a few cases have been reported about this bacterium infecting the human body, but most reports are mainly about sepsis. We will report on a woman with lymphoma who was successfully diagnosed by the use of transbronchial cryobiopsy (TBCB) with L. pseudomesenteroides pulmonary infection.